Neurotoxic side effects in children with refractory or relapsed T‐cell malignancies treated with nelarabine based therapy. (2nd August 2017) - Kuhlen, Michaela; Bleckmann, Kirsten; Möricke, Anja; Schrappe, Martin; Vieth, Simon; Escherich, Gabriele; Bronsema, Annika; Vonalt, Annika; Queudeville, Manon; Zwaan, C. Michel; Ebinger, Martin; Debatin, Klaus‐Michael; et al.
Summary: The prognosis in children with refractory or relapsed (r/r) T‐cell acute lymphoblastic leukaemia (T‐ALL) or lymphoblastic lymphoma (T‐LBL) is poor. Nelarabine (Ara‐G) has successfully been used as salvage therapy in these children, but has been associated with significant, even fatal, neurotoxicities. We retrospectively analysed 52 patients with r/r T‐ALL/T‐LBL aged ≤19 years who were treated with Ara‐G alone ( n = 25) or in combination with cyclophosphamide and etoposide ( n = 27). The majority of patients (45/52) received 1–2 cycles of Ara‐G. Seventeen patients (32·7%) had refractory disease, 28 (53·8%) were in first relapse and 7 (13·5%) were in second relapse. A response to Ara‐G was achieved in 20 patients and 15 (28·8%) were in remission at last follow‐up. Twelve patients (23·1%) had neurotoxic adverse effects (neuro‐AE) of any grade, of whom 7 (13·5%) developed neurotoxicity ≥ grade III. The most frequent neuro‐AEs were peripheral motor neuropathy (19·2%), peripheral sensory neuropathy (11·5%) and seizures (9·6%). Three patients died of central neuro‐AE after 1–2 cycles of combination therapy. Patients with neurotoxicity were significantly older (median 15·17 years) than those without (10·34 years, P = 0·017). No differences were observed between mono‐ and combination therapy concerning outcome and neuro‐AE. The incidence of neuro‐AE was not associated with concurrent intrathecal therapy or prior central nervous system irradiation.